Mapping health assessment questionnaire disability index onto EQ-5D-5L in China - Wan, Chuchuan; Wang, Qiqi; Xu, Zhaoqi; Huang, Yuankai; Xi, Xiaoyu (Frontiers in Public Health, 2023)
Objective: This research aimed to develop the more accurate mapping algorithms from health assessment questionnaire disability index (HAQ-DI) onto EQ-5D-5L based on Chinese Rheumatoid Arthritis patients. Methods: The cross-sectional data of Chinese RA patients was used for constructing the mapping algorithms. Direct mapping using Ordinary least squares regression (OLS), the general linear regression model (GLM), MM-estimator model (MM), Tobit regression model (Tobit), Beta regression model (Beta) and the adjusted limited dependent variable mixture model (ALDVMM) and response mapping using Multivariate Ordered Probit regression model (MV-Probit) were carried out. HAQ-DI score, age, gender, BMI, DAS28-ESR and PtAAP were included as the explanatory variables. The bootstrap was used for validation of mapping algorithms and mean absolute error (MAE), root mean square error (RMSE), adjusted R2 (adjR2) and concordance correlation coefficient (CCC) were used to assess the predictive ability of the mapping algorithms. Results: According to the average rank of MAE, RMSE, adjR2 and CCC, the mapping algorithm based on Beta performed the best. And the mapping algorithm performed better as the number of variables increasing. Conclusion: The mapping algorithms provided in this research can help researchers to obtain the health utility values more accurately. And researchers can choose the mapping algorithms under different combinations of variables based on the actual data.